IMPLEMENTING A COMPREHENSIVE QUALITY ASSURANCE PROGRAM IN A RADIOLOGY DEPARTMENT: A COLLABORATIVE APPROACH - Khalid Matar Sayih Alanazi, Ahmed Mohammed N Alshammari, Fahad Saad A Alanazi, Khaled Awad H Alenazi, Khaled Faza Alshamari, Homoud Mutlaq A Almutairi, Muneef Khalid N Alsewait, Nassir Farhan M Alanazi (Chelonian Research Foundation, 2022)
Quality assurance (QA) programs are essential for ensuring the delivery of high-quality and safe radiological services. Implementing a comprehensive QA program requires a collaborative approach involving all stakeholders in the radiology department. This study describes the development and implementation of a QA program at the radiology department of King Khaled General Hospital in Hafar Albatain, Saudi Arabia. The program was designed and implemented by a multidisciplinary team of radiologists, technologists, physicists, and administrators. The QA program included elements such as equipment quality control, radiation safety, patient safety, staff training and education, and continuous quality improvement. The implementation of the program resulted in significant improvements in image quality, radiation dose optimization, patient satisfaction, and overall efficiency of the department. The collaborative approach was key to the successful implementation and sustainability of the QA program. This study provides a model for other radiology departments seeking to implement a comprehensive QA program and highlights the importance of collaboration in achieving quality and safety goals.